VISITE DES LIEUX DANS LE RESSORT DU TRIBUNAL DE GRANDE INSTANCE D’ISIRO : UN CASSE – TETE POUR LES JUGES ET POUR LES JUSTICIABLES DE 2014 A 2017. - Oseyatoko, Marcel (IJRDO - Journal of Social Science and Humanities Research, 2019)
The present research has the problem of verifying why the visit of the place is a puzzle for the judges and for the litigants within the jurisdiction of the High Court of Isiro from 2014 to 2017. Thus, through this investigation, we seek to find these puzzles and suggest possible solutions. At the end of our research, we confirmed all our initial hypotheses because it emerged that the refusal to testify; the lack of logistical means of magistrates, the low purchasing power of the population are the main causes of the blocking of descent on the spot.